Incidence and Outcomes of Severe Anaphylaxis in Paediatric Patients in Atlantic Canada - Krmpotic, Kristina; Weisser, Caroline; O'Hanley, Alexandra; Soder, Christian (Journal of Pediatric Intensive Care, 2019)
Little is known about severe anaphylaxis in the pediatric population. In this retrospective cohort study, we aimed to describe the characteristics of children who required admission from an outpatient setting to one of two Pediatric Intensive Care Units in Atlantic Canada with a primary diagnosis of anaphylaxis. During the 10-year study period, there were 12 admissions (58% females) for a population incidence of 2.4 per 100,000 children. Both patients who died were adolescents with a witnessed anaphylaxis event, immediately recognized as such after exposure to a known allergen, with immediate access to epinephrine that was not administered until after cardiorespiratory arrest occurred. This study highlights the high mortality associated with severe anaphylaxis and the ongoing need for education surrounding the early administration of intramuscular epinephrine.
Keywords: anaphylaxis; child; critical care; management; pediatric